Congruent aero-tactile stimuli bias perception of voicing continua - Goldenberg, Dolly; Tiede, Mark K.; Bennett, Ryan T.; Whalen, D. H. (Frontiers in Human Neuroscience, 2022)
Multimodal integration is the formation of a coherent percept from different sensory inputs such as vision, audition and somatosensation. Most research on multimodal integration in speech perception has focused on audio-visual integration. In recent years, audio-tactile integration has also been investigated, and it has been established that puffs of air applied to the skin and timed with listening tasks shift the perception of voicing by naive listeners. The current study has replicated and extended these findings by testing the effect of air puffs on gradations of voice onset time along a continuum rather than the voiced and voiceless endpoints of the original work. Three continua were tested: bilabial (“pa/ba”), velar (“ka/ga”), and a vowel continuum (“head/hid”) used as a control. The presence of air puffs was found to significantly increase the likelihood of choosing voiceless responses for the two VOT continua but had no effect on choices for the vowel continuum. Analysis of response times revealed that the presence of air puffs lengthened responses for intermediate (ambiguous) stimuli and shortened them for endpoint (non-ambiguous) stimuli. The slowest response times were observed for the intermediate steps for all three continua, but for the bilabial continuum this effect interacted with the presence of air puffs: responses were slower in the presence of air puffs, and faster in their absence. This suggests that during integration auditory and aero-tactile inputs are weighted differently by the perceptual system, with the latter exerting greater influence in those cases where the auditory cues for voicing are ambiguous.